East Timor : The Price of Freedom - Taylor, John G., 1947- (London Zed Books, 1999)
"In this updated and much expanded edition of his book, Indonesia's Forgotten War: The Hidden History of East Timor, John Taylor tells in detail the story of what happened to this island people following President Suharto's downfall in the wake of the Asian economic crisis. The new Indonesian government conceded the right of the United Nations to organise the long delayed referendum giving the East Timorese a choice between continued association with Indonesia or independence.
Include Bibliography and Index
Keywords: Timor-Leste -- Politics and Government -- East Timor -- Politics and Government -- Politics and Government